The Use of Artificial Intelligence and Accounting Information Systems as Tools to Improve Employee Productivity in MSMEs in Medan Area - Wijaya, Florence Utari; Yonson Pane (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
This study aims to determine whether Artificial Intelligence and Accounting Information Systems have a significant effect on Employee Productivity in MSMEs in Medan Area. This research uses a quantitative approach conducted on MSMEs spread across the Medan Area area from June 2024 to October 2024. The population of this study were MSMEs spread across the Medan Area which amounted to 1,875 MSMEs. The sample was obtained using the Slovin formula with a percentage error of 10% so that a sample of 95 MSMEs was obtained. The collection technique used was purposive or judgmental sampling. Data analysis and testing consists of validity tests, reliability tests, descriptive statistical tests, classical assumption tests, multiple linear regression analysis, partial (T test) and simultaneous (F test) hypothesis testing, and determination coefficient tests. The results showed that Artificial Intelligence has a significant effect partially on Employee Productivity with a tcount value of 9.979> t table 1.986. The results showed that the Accounting Information System has a significant effect partially on Employee Productivity with a tcount of 2.992> t table 1.986. Artificial Intelligence and Accounting Information Systems simultaneously have a significant influence on Employee Productivity with an Fcount value of 149.280> Ftable value of 3.10 and a regression coefficient value of 76.4%.